First Report of a Sea Louse, Lepeophtheirus salmonis, Infestation on Juvenile Pink Salmon, Oncorhynchus gorbuscha, in Nearshore Habitat - Morton, Alexandra B.; Williams, Rob (The Canadian Field-Naturalist, 2003)
High infestation rates of the Sea Louse (Lepeophtheirus salmonis) have been reported on juvenile salmonids in Europe since 1989; however, this species has not been reported on juvenile Pacific salmonids until now. Magnitude of Sea Lice infestation was examined in 2001 on juvenile Pink Salmon (Oncorhynchus gorbuscha) migrating through a British Columbia archipelago. On average, the 751 juvenile Pink Salmon sampled weighed 2.25 g (± 0.039 SE), were infected with 11.3 (± 0.41 SE) Sea Lice per fish and 6.1 (± 0.24SE) Sea Lice per gram host weight. Fully 75.0% of fish were infected at loads equivalent to or higher than the lethal limit reported for much larger Sea Trout (Salmo trutta) post-smolts. Abundance (Kruskal-Wallis statistic = 100.95, p<0.0001) and intensity (KW= 70.05, p<0.0001) of lice, and mean number of lice/g host weight (K-W= 112.23, p<0.0001) were significantly higher in juvenile Pink Salmon in close proximity to salmon farms, than in Pink Salmon distant from salmon farms.